Evaluating low-cost ARM SBCs as video-capture nodes in a vehicular panoramic video recording system - Chua, Koon Ming (2014)
An increasing numbers of vehicles are being fitted with cameras to provide a video log that may be used in case of accidents on the road. These cameras typically capture only one view (forward-looking) with a limited field of view and poor low-light performance. Furthermore, they typically do not have much redundancy.